The betrayal of the humanities the university during the Third Reich - Levinson, Bernard M. 1952-; Ericksen, Robert P. 1945- (Studies in Antisemitism, 2022)
Cover -- Title Page -- Copyright -- Contents -- Contributors -- Illustrations -- Abbreviations -- Preface -- Introduction: The Betrayal of the Humanities under National Socialism / Bernard M. Levinson and Robert P. Ericksen -- Part I. Nazi Germany and the Historical Humanities -- 1. The History of the Humanities in the Third Reich / Alan E. Steinweis -- 2. The "Orient" and "Us": Making Ancient Oriental Studies Relevant during the Nazi Regime / Suzanne L. Marchand -- 3. Luther Scholars, Jews, and Judaism during the Third Reich:From the Hallowed Halls of Academia to the Sacred Spaces of German Protestantism / Christopher J. Probst -- 4. Gerhard von Rad's Struggle against the Nazification of the Old Testament / Bernard M. Levinson -- 5. Jewish Studies in the Service of Nazi Ideology: Tübingen's Faculty of Theology as a Center for Antisemitic Research / Anders Gerdmar -- 6. Hermann Grapow, Egyptology, and National Socialist Initiatives for the Humanities / Thomas Schneider -- 7. German Assyriology: A Discipline in Troubled Waters / Johannes Renger -- 8. National Socialist Archaeology as a Faustian Bargain: The Contrasting Careers of Hans Reinerth and Herbert Jankuhn / Bettina Arnold -- Part II. Law, Music, and Philosophy in the Third Reich -- 9. Hitler's Willing Law Professors / Oren Gross -- 10. The Music of Arnold Schoenberg: Catastrophe and Creation / Michael Cherlin -- 11. Political Philosophy: Hannah Arendt and Aurel Kolnai as Interpreters of the Nazi Totalitarian State / Emmanuel Faye -- Part III. Nazi Germany and Beyond -- 12. The Nazification and Denazification of the University of Göttingen / Robert P. Ericksen -- 13. The University of Göttingen and Its Postwar Response to Persecuted Colleagues: A Broken Relationship / Anikó Szabó.